Islamic Communication in Empowering Muhammadiyah Farmer Communities toward Sustainable Food Security - Khoirurrosyidin Khoirurrosyidin; Tobroni Tobroni (Universitas Darussalam Gontor, 2026)
This study aims to describe the concept of food security through the empowerment of Jamaah Tani Muhammadiyah (JaTaM) as a productive da’wah model that integrates religious, social, and economic values. The research employs a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and documentation. The informants include the Head of JaTaM, active farmer members, representatives from the Muhammadiyah Community Empowerment Council (MPM), agricultural officials, and local community members involved in JaTaM activities. The findings show that JaTaM’s concept of food security is built on three main pillars: production, distribution, and consumption, which are collectively managed through a community-based cooperative. The farmer empowerment programs include organic farming training, collective land management, a community food savings system, and the “Joint Harvest” event that strengthens member solidarity. The implementation of these programs has led to increased economic independence, stronger social bonds, and enhanced spiritual awareness that farming is a form of worship and economic jihad. Furthermore, JaTaM has become a strategic partner of local governments in promoting community-based food security and expanding its impact to the village level. The study concludes that JaTaM empowerment model successfully achieves sustainable food security through the synergy of Islamic values, mutual cooperation, and local economic independence. Keywords: Food security, farmer empowerment, Jamaah Tani Muhammadiyah, economic independence, productive da’wah